2020
DOI: 10.1093/trstmh/traa041
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms associated with quinolone resistance in Enterobacteriaceae: review and update

Abstract: Abstract Background Quinolones are broad-spectrum antibiotics, which are used for the treatment of different infectious diseases associated with Enterobacteriaceae. During recent decades, the wide use as well as overuse of quinolones against diverse infections has led to the emergence of quinolone-resistant bacterial strains. Herein, we present the development of quinolone antibiotics, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 153 publications
0
13
0
1
Order By: Relevance
“…Data in Table 3 indicated that ciprofloxacin is the last barrier to eliminating antibiotic resistance Vibrio. Ciprofloxacin has stronger antibacterial activity than antibiotics of other groups such as amino acids, β-lactams, tetracyclines, and penicillins [17,18]. Ciprofloxacin inhibited bacteria growth through inactivation of the DNA gyrase, which further prevents chromosome replication [17].…”
Section: Discussionmentioning
confidence: 99%
“…Data in Table 3 indicated that ciprofloxacin is the last barrier to eliminating antibiotic resistance Vibrio. Ciprofloxacin has stronger antibacterial activity than antibiotics of other groups such as amino acids, β-lactams, tetracyclines, and penicillins [17,18]. Ciprofloxacin inhibited bacteria growth through inactivation of the DNA gyrase, which further prevents chromosome replication [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, for CIP resistance, all of the isolates were annotated to the fluoroquinolone-resistant efflux pump CRP and rsm A. The efflux pump is the principal mechanism of intrinsic and acquired AMR in clinical infections ( Azargun et al, 2020 ). It has substrate specificity and can excrete a variety of toxic compounds from bacterial cells, causing MDR.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] In addition there is a co-existence with other antibiotics including Aminoglycosides and Fluoroquinolones. [25][26] These isolates exhibit decrease Ciprofloxacin susceptibility (DCS, MIC value 0.38mg/L) and Luminex based assay to detect mutations in quinolone resistant determining regions (QRDR) and plasmid mediated quinolone resistant gene (PMQR) reveal that DCSs was linked with the single mutation in residue ser83 of gyrA gene. This is one of the prominent genetic elements among salmonella typhi (S. Typhi) exhibiting DCS.…”
Section: Epidemiology Of Ctx-m -Lactamase-producing Bacteriamentioning
confidence: 99%